The determinant effect of industry sub-sectors on the gross regional domestic product in Maluku - Teddy Christianto Leasiwal (Journal of Economics, Business, and Accountancy Ventura, 2015)
The development that takes place in a province as a whole and sustainable society has improved the economy. The achievement of development outcomes are strongly felt by society as the aggregate of development of 11 districts or cities in the province of Maluku which is inseparable from the endeavors jointly undertaken between the government and society. GDP of Maluku province is ranked 31 out of 33 provinces in Indonesia, an interesting problem to be studied, when considering the natural resources, infrastructure support, and even the location of Maluku as the archi-pelago. This is considered to have strategic value. This study uses panel data to measure GDP growth through industrial sector based on the effect of investment, employment, and the number of companies located in it. The results show that the number of the companies, labors, and investment, in general industrial subsector, have effect on the increase in GDP, which in turn can affect the economic growth in Maluku.